An Approach to Design Power Management Structure for Hybrid Power Systems: A case study on Wind-Battery-Ultracapacitor Hybrid Power System - Boynuegri, Ali Rifat; Eren, Yavuz (IEEE, 2018)
Despite the fact that, a great number of utility models powered by renewable energy sources have been penetrated into the grid or off grid power sources, it is already an important problem to meet the demanded power by those sources in a sustainable way. Therefore, the research on power management structure for hybrid power system (HPS) have been focused by the researchers. In the view of the related studies, we proposed a novel approach to design power management scheme that is applicable to any such HPS. This approach is based on choosing the DC bus voltage in the power conditioning system as rectified sinusoidal wave form so as to use such an inverter which provides to switch at 50 Hz and synthesizing PI type controllers to regulate the voltage on the bus. By the merits of low switching inverter and controller design, we claim that this novel approach not only gives rise to recovery in the power quality, as well as, it does not need necessitate to design filter at the output of the inverter.
Keywords: Energy management system; Polarity changing inverter; Sinusoidal DC Bus; WT/Battery/UC hybrid power system; Computer Science; Energy & Fuels